The interference of fiscal regulations with those in the criminal field. The right to silence and the right not to self-incriminate of a legal person in Romania - Mihes , Christian; Cirmaciu, Diana (European Integration Studies, 2023)
In our approach, some aspects must be clarifies from the beginning, regarding a prerogative of the financial (fiscal) authority, but also of the tax system, respectively the control function. The Tax Procedure Code regulates the procedures by which the tax bodies verify the fulfilment by the persons subject to the tax law of the legal obligations. These procedures are the followings i.e. tax inspection, unexpected control, verification of the personal tax situation by the central tax body, anti-fraud control, and documentary verification. Each procedure is governed by specific rules and objectives. Also, the issues of taxpayer’s right to present his point of view on the relevant facts and circumstances are going to be addressed, and of course, the taxpayer’s obligation to cooperate versus the right to silence and plea-agreement.